The High Level of Tertiary Lymphoid Structure Is Correlated With Superior Survival in Patients With Advanced Gastric Cancer - He, Wenting; Zhang, Dachuan; Liu, Hong; Chen, Tongbing; Xie, Jun; Peng, Lei; Zheng, Xiao; Xu, Bin; Li, Qing; Jiang, Jingting (Frontiers in Oncology, 2020)
Background: A tertiary lymphoid structure (TLS) is a crucial component of the tumor microenvironment (TME), which reflects the anti-tumor immune response in the host. This aim of the present study was to carry out a histopathological evaluation for TLS and assess its prognostic value in gastric cancer (GC). Methods: A total of 1,033 cases that has received a gastrectomy were reviewed, including 914 in the primary cohort and 119 in the validation cohort. TLS was assessed by optical microscopy and verified by immunohistochemistry. A total of 5 histopathological evaluation methods were compared in the primary cohort and validated in the validation cohort. In addition, MECA-79 and CD21 were used to verify the accuracy of the histopathological scoring system for TLS. The association among TLS, clinicopathological parameters and patient prognosis was analyzed. Results: TLS assessed by morphology and immunohistochemistry were significantly correlated and consistent. The morphological evaluation of TLS was accurate. Typically, the high level of TLS was significantly correlated with tumor size (P=0.047), histological grade (P=0.039), pTN stage (P=0.044), and WHO subtype (P<0.001). In addition, TLShi was a positive indicator of overall survival (OS), as determined by Kaplan-Meier survival (P=0.038) and multivariate Cox regression analysis (HR=0.794, 95% CI: 0.668-0.942, P=0.008). According to the results, TLShi had a positive effect on primary cohort patients with pTN stage II and III (P=0.027, P=0.042). Conclusions: The histopathological evaluation of TLS was accurate. Diagnosis based solely on Hematoxylin and Eosin staining of sections did not easily distinguish tumor-associated TLS. The density of TLS in the center of the tumor was found to be more indicative of patient prognosis than TLS in the invasive margin, with levels of total TLS shown to best correlate with overall survival in patients with advanced-stage GC.